Les risques de produits et les tendances nouvelles en assurance - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1981)
The author has summarized in his article the present situation in the products liability insurance in the United States and Canada. As there is a very close connection between our two countries, we are sure that the reader shall appreciate Mr. Moreau's views on the subject. The market for products liability in the United States has been narrowing from year to year due to certain circumstances which have given rise to various claims which have been costly to the insurance community. For this reason, products liability insurance is hard to obtain in certain cases and is also very costly, with exclusions which very few insurers accept to withdraw from the policy. There are, however, new tendancies which the author has developed in his article. A.